Method for controllably preparing magnetic nanofiber film through current regulation and control magnetic field auxiliary electrospinning

Through the current-controlled magnetic field-assisted electrospinning technology, the problems of inaccurate magnetic field regulation and poor stability in the existing technology are solved, and efficient, precise preparation and performance improvement of nanofibers are achieved, and are suitable for many high-end fields.

CN119571477AActive Publication Date: 2025-03-07DONGHUA UNIV

Patent Information

Application Number
CN202411883257.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing magnetic field-assisted electrospinning technology has problems such as limited magnetic field strength and uniformity, poor stability and controllability, and limited magnetic field range, which affects the precise regulation and preparation efficiency of fibers.

Method used

The current-controlled magnetic field-assisted electrospinning technology is used to control the intensity and direction of the magnetic field by precisely adjusting the current. The magnetic field generated by the electromagnetic lens plays a role in the electrospinning process, achieving accurate regulation of fiber arrangement, deposition and magnetic properties.

Benefits of technology

It significantly improves the overall stability and controllability of electrospinning technology, optimizes the preparation accuracy and efficiency of nanofiber films, improves the performance of magnetic nanofibers, and is suitable for high-performance composite materials and biomedicine fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571477A_ABST
    Figure CN119571477A_ABST
Patent Text Reader

Abstract

The invention relates to a method for controllably preparing a magnetic nanofiber film by current regulation and control magnetic field assisted electrospinning, which comprises the following steps: weighing PAN white powder, dissolving in a DMF organic solvent, continuously stirring by magnetic field force, and carrying out ultrasonic dispersion treatment on the solution by using an ultrasonic cleaner to prepare a uniformly dispersed PAN / DMF solution; adding Fe3O4 nanoparticles and a dispersing agent Triton X-100 with the same amount as the Fe3O4 nanoparticles into the prepared solution, and performing ultrasonic dispersion treatment to form a uniformly dispersed magnetic electrostatic spinning solution; according to the prepared magnetic electrostatic spinning solution, a thin and uniform high-performance magnetic nanofiber sample is prepared through a controllable magnetic field generated by a current control electromagnetic lens to assist an electrostatic spinning device, the thin and uniform high-performance magnetic nanofiber sample is placed in a drying box to be dried, and the thin and uniform high-performance magnetic nanofiber sample with the reduced deposition circle area, the increased thickness, the increased mechanical property, the improved magnetic property and the high-performance magnetic performance is obtained. The average diameter of the nanofibers is reduced and the nanofibers are uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional nanofiber manufacturing, and in particular relates to a method for controllably preparing a magnetic nanofiber film by current-regulated magnetic field-assisted electrospinning. Background Art

[0002] Electrospinning technology, as an efficient and flexible process for preparing nanofibers, has shown great application potential in many fields such as materials science, biomedicine, and environmental protection. Traditional electrospinning technology mainly relies on electric field forces to stretch and refine the spinning solution to form nanofibers. However, during the spinning process, the arrangement and deposition of fibers are often affected by multiple factors such as electric field distribution, spinning solution properties, and environmental parameters, resulting in disordered fiber arrangement, uneven diameter distribution, and difficulty in achieving orderly arrangement on a macro scale. These problems limit the application of nanofibers in high-end fields, such as high-performance composite materials and biomedical implants.

[0003] In order to overcome the limitations of traditional electrospinning technology, researchers began to try to introduce magnetic fields into the electrospinning process. Magnetic field-assisted electrospinning technology achieves precise control of fiber arrangement and deposition by applying a magnetic field in the spinning area and using the attraction and repulsion of the magnetic field on the charged fibers. This method can not only improve the orderliness of the fibers, but also control the diameter and morphology of the fibers, thereby preparing nanofibers with excellent performance and specific structures. However, there are still some problems with the existing magnetic field-assisted electrospinning technology. Chinese invention patent CN118029620A discloses a highly flame-retardant and anti-corrosion glass fiber asphalt shingle and a preparation method thereof, wherein the preparation of the glass fiber asphalt shingle is obtained by using a magnetic field-assisted electrospinning technology generated by a magnet. Chinese invention patent CN113897690A discloses a method for preparing ordered PVDF nanofibers based on magnetic field-assisted electrospinning, which also uses a magnetic field-assisted electrospinning preparation generated by a magnet. Chinese invention patent CN103060933B discloses a method for preparing polymer micro-nano composite fibers, which is to prepare nanofibers by adding magnetic nanoparticles and a magnetic field generated by a magnet. Although the magnetic field generated by the magnet can affect the arrangement and deposition of fibers during electrospinning to a certain extent, this method still exposes several significant disadvantages in practical applications. First, the magnetic field strength and distribution generated by the magnet are often difficult to achieve an ideal state. Due to the limitations of the physical properties of the magnet, the magnetic field strength and uniformity it generates may not meet the needs of precise control of fibers during electrospinning. Secondly, the stability and controllability of the magnet's magnetic field are poor, and the magnetic field strength is easily affected by ambient temperature, humidity, and other surrounding magnetic field sources, resulting in fluctuations in fiber orientation and deposition patterns during the spinning process. Finally, the magnetic field generated by the magnet has a limited range and may not cover the entire preparation area, which requires frequent adjustments to the position and number of magnets during the preparation process, which not only increases the complexity of the operation, but may also affect the preparation efficiency. Chinese patent ZL201020033366.6 proposes to add a static magnetic field with adjustable magnetic field strength during the polymer jet stretching process to improve the crystallization behavior of the polymer and make up for the shortcomings of traditional electrospun fibers such as low crystallinity and poor mechanical strength. However, the magnetic field adjustment of this patent is still to adjust the magnetic field strength by moving the sliding magnet up and down and horizontally on the bracket. This manual adjustment method is relatively cumbersome and has limited adjustment accuracy. The sliding magnet is limited by its physical properties (such as magnetization strength and size) and is difficult to generate a high-intensity or rapidly changing uniform magnetic field, which may cause the polymer jet to be subjected to uneven magnetic field forces during the stretching process, thereby affecting the fiber quality.

[0004] In summary, although magnetic field-assisted electrospinning technology has the potential to improve fiber performance, the existing magnetic field is basically generated by magnets. This method has problems such as limited magnetic field intensity and uniformity, poor stability and controllability, and limited magnetic field range, which affect the precise regulation and preparation efficiency of the fiber. Therefore, the development of more efficient, stable and controllable magnetic field regulation technology is crucial to promote the development of magnetic field-assisted electrospinning technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and seek to design and provide a method for the controllable preparation of magnetic nanofiber films by current-controlled magnetic field-assisted electrospinning. The present invention adopts an advanced current-controlled magnetic field-assisted electrospinning device, which flexibly controls the magnetic field strength by precisely adjusting the current, thereby playing a dual role in the electrospinning process: on the one hand, it enhances the electron aggregation effect on the surface of the charged jet during the electrospinning process; on the other hand, it effectively guides the directional arrangement of magnetic nanoparticles. The present invention not only significantly improves the overall stability and controllability of electrospinning technology, but also greatly optimizes the accuracy and efficiency of nanofiber film preparation, opening up a new way for the large-scale, high-quality production of magnetic nanofibers.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for controllably preparing a magnetic nanofiber film by current-controlled magnetic field-assisted electrospinning, comprising the following steps:

[0008] Step (1) Preparation of spinning solution: Weigh polyacrylonitrile (PAN) powder and dissolve it in N,N-dimethylformamide (DMF) organic solvent, stir it continuously with magnetic field force, and then use ultrasonic cleaner to ultrasonically disperse the solution to prepare a uniformly dispersed PAN / DMF solution. Then add Fe3O4 nanoparticles and an equal amount of dispersant Triton X-100 to the prepared solution, and then perform ultrasonic dispersion treatment to form a uniformly dispersed magnetic electrospinning solution;

[0009] Step (2) Device adjustment: fix the syringe firmly on the micro-injection pump, adjust the distance between the syringe needle and the collector, and the distance between the electromagnetic lens and the collector, then connect the positive line of the DC high-voltage power supply to the syringe, and the negative line to the collector, set the propulsion rate of the micro-injection pump, and the current of the electromagnetic lens to 1A, and finally turn on the DC high-voltage power supply;

[0010] Step (3) Preparation of nanocomposite fibers: With the start-up of the microinjection pump, the prepared magnetic PAN / DMF / Fe3O4 magnetic electrospinning solution gathers at the needle tip of the syringe. Under the combined action of the high-voltage electrostatic field force and the controllable magnetic field force generated by the electromagnetic lens, the droplets form a charged jet that is transferred to the collecting electrode, thereby controllably preparing a magnetic nanofiber film.

[0011] Compared with the prior art, the present invention has the following advantages:

[0012] (1) The present invention adopts current control technology to achieve precise regulation of the magnetic field. By adjusting the magnitude and direction of the current, the strength and direction of the magnetic field can be precisely controlled, thereby meeting the precise requirements for fiber arrangement, deposition and magnetic properties during the electrospinning process.

[0013] (2) Improved magnetic field stability and controllability. Compared with the traditional method of generating magnetic fields with magnets, current-controlled magnetic fields have higher stability and controllability. They are not easily affected by ambient temperature, humidity, and external magnetic field sources, and can ensure stable output of magnetic field strength during the spinning process, thereby improving the stability of fiber orientation and deposition pattern.

[0014] (3) The magnetic field range is expanded and uniform. The magnetic field generated by the current regulation of the present invention can cover the entire preparation area, and the magnetic field distribution is uniform. This avoids the need to frequently adjust the position and number of magnetic field generating devices, simplifies the preparation process, improves the preparation efficiency, and ensures the uniformity and consistency of the fibers in the entire spinning area.

[0015] (4) Optimizing the performance of magnetic nanofibers. By precisely controlling the magnetic field, the present invention can produce nanofibers with excellent magnetic properties. The magnetic field generated by the electromagnetic lens can reduce the average diameter of magnetic nanofibers prepared by electrospinning technology of PAN / DMF / Fe3O4 spinning solution by 5.1%, increase the average thickness by 92%, improve the mechanical properties by 19.3%, and increase the saturation magnetization by 56.5%. The magnetic parameters of these fibers, such as saturation magnetization, coercive force and remanence, can be significantly improved, thus having broad application prospects in the fields of magnetic recording materials, magnetic sensors, biomedicine, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A diagram of a device for a method for controllably preparing magnetic nanofiber film by current-regulated magnetic field-assisted electrospinning used in the present invention.

[0017] Figure 2 These are electron microscope (SEM) images of magnetic nanofiber films prepared under four different experimental conditions with / without magnetic spinning solution and with / without electromagnetic lens in the patent of this invention.

[0018] Figure 3This is a transmission electron microscope (TEM) image of a magnetic nanofiber film prepared under the experimental conditions of a magnetic spinning solution and an electromagnetic lens in the patent of the present invention.

[0019] Figure 4 This is a graph of the average diameter values ​​of nanofibers prepared under four different experimental conditions with / without magnetic spinning solution and with / without electromagnetic lens in the patent of this invention.

[0020] Figure 5 This is a graph of the average thickness of nanofibers prepared under four different experimental conditions with / without magnetic spinning solution and with / without electromagnetic lens in the patent of this invention.

[0021] Figure 6 This is a graph of the mechanical properties of nanofibers prepared under four different experimental conditions with / without magnetic spinning solution and with / without electromagnetic lens in the patent of this invention.

[0022] Figure 7 This is a graph of the magnetic energy values ​​of nanofibers prepared under four different experimental conditions with / without magnetic spinning solution and with / without electromagnetic lens in the patent of this invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below by way of examples and in conjunction with the accompanying drawings. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0024] like Figure 1As shown, a current-controlled magnetic field-assisted electrospinning device for preparing a magnetic nanofiber film comprises an electromagnetic lens 1, an electromagnetic lens power supply 2, an electromagnetic lens power supply positive line 3, an electromagnetic lens power supply negative line 4, a syringe 5, a syringe needle 6, a microinjection pump 7, a DC high-voltage power supply 8, a DC high-voltage power supply positive line 9, a DC high-voltage power supply negative line 10, a collector 11, a magnetic nanofiber jet 12, and a magnetic nanofiber film 13. The electromagnetic lens 1 is located between the syringe 5 and the collector 11, and the distance between the electromagnetic lens 1 and the collector 11 is 8 cm. The electromagnetic lens 1 is connected to the power supply through the electromagnetic lens power supply positive line 3 and the electromagnetic lens power supply negative line 4, and the magnitude of the current is adjusted to control the magnitude of the magnetic field intensity generated by the electromagnetic lens 1. The DC high-voltage power supply positive line 9 of the DC high-voltage power supply 8 is connected to the syringe needle 6, and the DC high-voltage power supply negative line 10 is connected to the collector 11, and the collector 11 is grounded. The syringe 5 gathers the magnetic spinning liquid on the syringe needle 6 under the action of the micro-injection pump 7. The magnetic spinning liquid droplets are transformed into charged jets under the action of the DC high-voltage power supply 8. The motion trajectory of the magnetic nanofiber jet 12 is changed under the action of the magnetic field generated by the electromagnetic lens 1, and finally falls on the collecting electrode 11 to form a magnetic nanofiber film 13.

[0025] A method for controllably preparing a magnetic nanofiber film by current-controlled magnetic field-assisted electrospinning, comprising the following steps:

[0026] Step (1) Preparation of spinning solution: Weigh polyacrylonitrile (PAN) powder and dissolve it in N,N-dimethylformamide (DMF) organic solvent, stir it continuously with magnetic field force, and then use ultrasonic cleaner to ultrasonically disperse the solution to prepare a uniformly dispersed PAN / DMF solution. Then add Fe3O4 nanoparticles and an equal amount of dispersant Triton X-100 to the prepared solution, and then perform ultrasonic dispersion treatment to form a uniformly dispersed magnetic electrospinning solution;

[0027] The mass ratio of the added Fe3O4 nanoparticles to the PAN powder is 1:0.2.

[0028] Step (2) Device adjustment: The syringe is firmly fixed on the micro-injection pump, and the distance between the syringe needle and the collector is adjusted to 16 cm, and the distance between the electromagnetic lens and the collector is 8 cm. Then, the positive line of the DC high-voltage power supply is connected to the syringe, and the negative line is connected to the collector. The propulsion rate of the micro-injection pump is set to 0.8 mL / h, the electromagnetic lens is powered on and the current is adjusted to 1 A. Finally, the DC high-voltage power supply is turned on and the voltage is set to 15 KV, so that a high-voltage electric field is formed between the syringe needle and the collector, and a magnetic field is introduced between the two through the electromagnetic lens device. The device adjustment is completed;

[0029] Step (3) Preparation of nanocomposite fibers: As the microinjection pump is started, the prepared spinning solution magnetic PAN / DMF / Fe3O4 spinning solution gathers at the syringe needle, and the droplets form a charged jet under the combined action of the high-voltage electrostatic field force and the controllable magnetic field force generated by the electromagnetic lens, which is transferred to the collecting electrode, thereby controllably preparing PAN / Fe3O4 magnetic nanofibers.

[0030] The inner diameter of the electromagnetic lens of the present invention is 188 mm, the excitation coil in the electromagnetic lens has 1360 turns, and the current of the electromagnetic lens is set to 1A.

[0031] The spinning time of the present invention is 2 hours, the spinning temperature is 25° C., and the spinning humidity is 40%.

[0032] The technical solution of the present invention is further described below in conjunction with embodiments:

[0033] Embodiment 1:

[0034] In this embodiment, the current of the electromagnetic lens is set to 0A, a PAN / DMF spinning solution without Fe3O4 nanoparticles is prepared, and a nanofiber film is prepared under the parameters of an electrospinning voltage of 15Kv, a distance between the needle and the collector of 16cm, and a propulsion rate of 0.8mL / h for 2 hours.

[0035] Embodiment 2:

[0036] In this embodiment, the current of the electromagnetic lens is set to 1A, and a PAN / DMF spinning solution without Fe3O4 nanoparticles is prepared. The nanofiber film is prepared under the parameters of electrospinning voltage of 15Kv, distance between needle and collector of 16cm, distance between electromagnetic lens and collector of 8cm, and needle advancement rate of 0.8mL / h for 2 hours.

[0037] Embodiment 3:

[0038] In this embodiment, the current of the electromagnetic lens is set to 0A, and a PAN / DMF / Fe3O4 spinning solution containing Fe3O4 nanoparticles is prepared. A magnetic nanofiber film is prepared under the conditions of electrospinning parameters of voltage 15Kv, distance between the needle and the collector of 16cm, and propulsion rate of 0.8mL / h for 2 hours.

[0039] Embodiment 4:

[0040] In this embodiment, the current of the electromagnetic lens is set to 1A, and a PAN / DMF / Fe3O4 spinning solution containing Fe3O4 nanoparticles is prepared. The magnetic nanofiber film is prepared under the conditions of electrospinning parameters of voltage 15Kv, distance between needle and collector 16cm, distance between electromagnetic lens and collector 8cm, and propulsion rate 0.8mL / h for 2 hours.

[0041] The fibers prepared in the above Examples 1-4 were subjected to SEM characterization, nanofiber diameter, nanofiber film thickness, deposition circle area, mechanical properties, and magnetic properties testing.

[0042] (1) SEM characterization: The morphology of the nanofibers prepared under four different experimental conditions, without / with magnetic spinning solution and without / with electromagnetic lens, in Examples 1-4 was observed using S-4800 SEM at a voltage of 5.0 kV and a magnification of 5.0 times. The diameters of 40 nanofibers prepared under the four conditions were measured using Image J. Figure 2 Shown are SEM images of nanofibers prepared under four different experimental conditions with / without magnetic spinning solution and with / without electromagnetic lens. Figure 2 Figure a is the SEM image of nanofibers prepared without magnetic spinning solution and electromagnetic lens. Figure 2 Figure b is the SEM image of nanofibers prepared under the conditions of magnetic spinning solution and no electromagnetic lens. Figure 2 Figure c is the SEM image of nanofibers prepared under the conditions of non-magnetic spinning solution and electromagnetic lens. Figure 2 Figure d is a SEM image of nanofibers prepared under the conditions of magnetic spinning solution and electromagnetic lens. Figure 2 It can be seen that when the electromagnetic lens device is not used, the fibers are sparse and thick as a whole. When the electromagnetic lens device is used, the nanofibers are dense and uniformly refined as a whole. The average diameter of the nanofibers is as follows Figure 4 As shown in the figure, under the condition of no magnetic spinning solution, the magnetic field generated by the electromagnetic lens can control the average diameter of the prepared nanofibers to be reduced by 6.0%, and under the condition of magnetic spinning solution, the magnetic field generated by the electromagnetic lens can control the average diameter of the prepared magnetic nanofibers to be reduced by 19.2%. It can be proved that regardless of whether the spinning solution contains magnetic nanoparticles, the electromagnetic lens will have a gathering effect on the electrospinning charged jet, and the effect of the electromagnetic lens on the charged jet with magnetic nanoparticles is more obvious.

[0043] (2) TEM characterization: The morphology of the nanofibers prepared under the conditions of magnetic spinning solution and electromagnetic lens in Example 4 was observed by TEM. Figure 3 As shown, it shows that magnetic nanoparticles are successfully doped into the nanofibers. Figure 3 Nanofibers prepared under the conditions of magnetic spinning solution and electromagnetic lens: a is a 500nm scale TEM image; b is a 100nm scale TEM image.

[0044] (3) Thickness test: The thickness of the nanofiber films prepared under four different experimental conditions, without / with magnetic spinning solution and without / with electromagnetic lens, in Examples 1-4 was tested using a thickness gauge. The samples under each experimental condition were tested ten times and the average value was taken. Figure 5The figure shows the average thickness values ​​of the nanofiber films prepared under four different experimental conditions: without / with magnetic spinning solution and without / with electromagnetic lens. By comparison, it is found that neither Example 1 (thickness is 160.71um) nor Example 3 (thickness is 169.80um) uses electromagnetic lens equipment to assist, and the thickness of the nanofiber films prepared under this condition is relatively low. When the electromagnetic lens is used to assist electrospinning to prepare nanofibers in Example 2 (thickness is 200.01um) and Example 4 (thickness is 326.50um), there are magnetic nanoparticles in the electrospinning ribbon jet. The magnetic field generated by the electromagnetic lens will not only aggregate the electrons on the surface of the electrospinning ribbon jet, but also have a directional guiding effect on the magnetic nanoparticles, so that the nanofibers are further controlled, causing the thickness to further increase.

[0045] (4) Deposition circle area measurement: The deposition circle areas of the nanofiber films prepared under four different experimental conditions, without / with magnetic spinning solution and without / with electromagnetic lens, in Examples 1-4 were measured and calculated using the measurement method. It was found that the deposition circle area of ​​Example 1 (414.690 cm 2 ) and Example 3 (deposition circle area is 343.219cm 2 ) did not use electromagnetic lens equipment to assist. Under this condition, the deposition circle area of ​​the nanofiber film prepared was larger. Example 2 (the deposition circle area was 240.332 cm 2 ) and Example 4 (deposition circle area is 164.934cm 2 ) When the electromagnetic lens assisted electrospinning to prepare nanofibers, the deposition circle area was further reduced. This indicates that the magnetic field generated by the electromagnetic lens has a dual effect on the magnetic nanofibers, thereby improving the further control of the electrospinning process.

[0046] (5) Mechanical properties test: The mechanical properties of the nanofiber films prepared under four different experimental conditions, without / with magnetic spinning solution and without / with electromagnetic lens, in Examples 1-4 were tested using a computerized tensile stress testing machine. The samples under each experimental condition were tested five times and the average value was taken. Figure 6 The figure shows the stress-strain value of the nanofiber film prepared under four different experimental conditions: without / with magnetic spinning solution and without / with electromagnetic lens. By comparison, it is found that neither Example 1 (stress is 2483.86KPa) nor Example 3 (stress is 911.13KPa) uses electromagnetic lens equipment to assist, and the mechanical properties of the nanofiber film prepared under this condition are relatively small. In Example 2 (stress is 2962.90KPa) and Example 4 (stress is 1299.32KPa), when the electromagnetic lens is used to assist electrospinning to prepare nanofibers, the mechanical properties are further improved, highlighting the effect of the magnetic field generated by the electromagnetic lens on the electrospinning ribbon jet.

[0047] (6) Magnetic property test: The magnetic properties of the nanofiber films prepared under four different experimental conditions, without / with magnetic spinning solution and without / with electromagnetic lens, in Examples 1-4 were tested using a comprehensive physical property measurement system. The magnetic property values ​​are shown in the figure below: Figure 7 As shown, it is known that the spinning solution in Example 1 and Example 2 does not contain magnetic nanoparticles, so the magnetic property is 0. The saturation magnetization intensity of the nanofiber prepared in Example 3 without using an electromagnetic lens is 1.86emu / g. The saturation magnetization intensity of the nanofiber prepared in Example 4 using an electromagnetic lens is 2.91emu / g. This shows that the electromagnetic lens can further control the motion trajectory of the electrospinning ribbon jet.

[0048] The invention discloses a method for preparing a magnetic nanofiber film by controlling the magnetic field assisted by current-controlled electrospinning, comprising the following steps: weighing PAN white powder and dissolving it in DMF organic solvent, stirring it continuously by magnetic field force, and then using an ultrasonic cleaner to perform ultrasonic dispersion treatment on the solution to prepare a uniformly dispersed PAN / DMF solution. Then, Fe3O4 nanoparticles and an equal amount of dispersant Triton X-100 are added to the prepared solution, and then subjected to ultrasonic dispersion treatment to form a uniformly dispersed magnetic electrostatic spinning solution; the prepared magnetic electrostatic spinning solution is used to prepare a fine and uniform high-performance magnetic nanofiber sample by a controllable magnetic field assisted electrostatic spinning device generated by a current-controlled electromagnetic lens, and the sample is placed in a drying oven for drying treatment to obtain a high-performance magnetic nanofiber film with a reduced deposition circle area, increased thickness, increased mechanical properties, improved magnetic properties, and a reduced and uniform average diameter of nanofibers. It not only promotes the progress of materials science, but also brings unprecedented development opportunities to multiple fields such as information technology, medical health, environmental protection, and new energy, heralding a more intelligent, green, and sustainable future.

[0049] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a magnetic nanofiber film by controlling the current and assisting the electrospinning process, characterized in that: The following steps are involved: Step (1) Preparation of spinning solution: Weigh polyacrylonitrile white powder and dissolve it in N,N-dimethylformamide organic solvent, stir it continuously with magnetic field force, and then use ultrasonic cleaner to ultrasonically disperse the solution to prepare a uniformly dispersed polyacrylonitrile / N,N-dimethylformamide solution. Then add Fe3O4 nanoparticles and an equal amount of dispersant Triton X-100 to the prepared solution, and then perform ultrasonic dispersion treatment to form a uniformly dispersed magnetic electrospinning solution; Step (2) Device adjustment: fix the syringe firmly on the micro-injection pump, adjust the distance between the syringe needle and the collector, and the distance between the electromagnetic lens and the collector; then connect the positive line of the DC high-voltage power supply to the syringe, and the negative line to the collector, set the propulsion rate of the micro-injection pump and the current of the electromagnetic lens; finally, turn on the DC high-voltage power supply; Step (3) Preparation of nanocomposite fibers: As the microinjection pump is started, the prepared magnetic polyacrylonitrile / N,N-dimethylformamide / Fe3O4 magnetic electrospinning solution gathers at the needle tip of the syringe. Under the combined action of the high-voltage electrostatic field force and the controllable magnetic field force generated by the electromagnetic lens, the droplets form a charged jet that is transferred to the collecting electrode, thereby controllably preparing a magnetic nanofiber film.

2. The method for preparing a magnetic nanofiber film by current-controlled magnetic field-assisted electrospinning according to claim 1, characterized in that: The mass ratio of the added Fe3O4 nanoparticles to the polyacrylonitrile powder is 1:0.

2.

3. The method for preparing a magnetic nanofiber film by current-controlled magnetic field-assisted electrospinning according to claim 2, characterized in that: The inner diameter of the electromagnetic lens is 188 mm, the excitation coil in the electromagnetic lens has 1360 turns, and the current of the electromagnetic lens is set to 1A.

4. The method for preparing a magnetic nanofiber film by current-controlled magnetic field-assisted electrospinning according to claim 1, characterized in that: The distance between the syringe needle and the collector is 16 cm.

5. The method for preparing a magnetic nanofiber film by controllable electrospinning assisted by current-controlled magnetic field according to claim 1, characterized in that: The distance between the electromagnetic lens and the collector is 8 cm.

6. The method for preparing a magnetic nanofiber film by controllable electrospinning assisted by current-controlled magnetic field according to claim 1, characterized in that: The parameters of the controllable magnetic field assisted electrospinning generated by the electromagnetic lens are: electrostatic high voltage of 15Kv, magnetic spinning liquid advancement rate of 0.8mL / h, spinning time of 2h, spinning temperature of 25°C, and spinning humidity of 40%.

Citation Information

Patent Citations

  • Electrostatic spinning device and method for preparing large-area oriented nanofiber membrane

    CN108588858A

  • Magnetic lens electrostatic spinning device

    CN113388899A

  • Electrostatic spinning needle head blockage remote regulation and control system based on pressure detection

    CN113388900A

  • System for taking nanofiber film through external magnetic field assisted microflow control and use method

    CN115652533A

  • Electrostatic spinning device under multi-field function

    CN201648580U

Cited By

  • Method for preparing high-quality nanofiber membrane by external magnetic field assisted electrostatic spinning technology

    CN121593236A